design and construct application analytics of poor families's data based on poverty's criteria Badan Pusat Statistik (BPS) at Banaran's Village kediri's county - Pradhana, Angga Yudha; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Poverty is a problem found in many developing countries, including Indonesia. In determining and collecting data of poor families do not involve the village government, so that the village government tried to involve themselves in this regard. It is expected by the village government involvement in terms of determining pendatan and poor families can improve the accuracy of data on poverty,however the village government had difficulty in the process. Process is done manually, ie the data rate family one by one with poverty criteria determined by the village. To help improve the process, developed an application using System Developmen Life Cycle (SDLC) and 14 criteria of poverty from the Badan Pusat Statistik (BPS) as an indicator of poverty assessment that is expected to help the village government in realizing the mission of the village in terms of poverty, which is to provide data poor families. Results from this study is the poverty status of each family. The resulting information can be used as a basis for determining the poverty reduction policies.Keywords: Application, Family, poverty